"How are You Doing?" on the Healthy Aging of the Community-Dwelling Oldest-Old in the Shadow of the COVID-19 Pandemic. (March 2023) - Lo, Shirley K.L.; Liu, Justina Y.W.; Cheung, Daphne S. K.; Yin, Yue-Heng; Ng, Siu Ying; P.K. Kor, Patrick; Yang, Lin; Chan, Siu Kay; Kwan, Rick Y.C.; Lee, Paul H.; Chiang, Vico C. L.
Objective: Globally, the oldest-old population is growing rapidly. Little is known about the perceived well-being of the community-dwelling oldest-old, especially during the COVID-19 pandemic. This study examined the oldest-old's perceptions of aging well and the COVID-related impacts on them. Methods: Semi-structured in-depth interviews with 22 adults aged 85 or above were conducted with purposive sampling methods. Transcripts were analyzed using thematic analysis. Results: Four main themes emerged: 1) sustaining functional ability; 2) staying active with a positive attitude; 3) feeling grateful for support from society and family; 4) COVID-19-related anxieties and policies destabilizing their well-being. Discussion: This study provides direct evidence from the oldest-old on how they maintained their well-being. While they valued support from society and family, COVID-19-related measures disturbed their routines and prevented them from self-attaining well-being. The findings should be considered when developing interventions for this vulnerable group.